Implementasi fuzzy servqual dalam evaluasi kualitas pelayanan penyuluh pertanian - Dewi Suranti; Yupianti Yupianti (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2019)
This study aims to measure the quality of service of agricultural extension workers at the UPT. BPP Sukaraja uses the fuzzy service quality (servqual) method by grouping question attributes into five service dimensions criteria, namely the dimensions of tangibles (direct evidence), reliability (responsibility), responsiveness, assurance, and empathy. The study showed that the value of the gap that requires the priority of improvement and improvement in service quality is the dimension of Tangibles with a negative gap value of -0.45 that means that the expectations of farmers are still not achieved. The customer satisfaction index is 87.93%, which means farmers are satisfied with the services provided. The study can be a motivation to improve the quality of service to farmers for UPT BPP Sukaraja.